Impurity of dust-acoustic plasma instability due to trapped ions - El-Shorbagy, Kh H. (2008)
Summary: We are investigating the low-frequency electrostatic perturbation in tokamak plasma in the "banana" regime by taking account the effects of the Coulomb collision on the trapped ion. We consider the dust-acoustic plasma instability caused by the presence of ion impurities. We point out that the presence of impurity ions, especially if their density gradient is different from the dust plasma density gradient, i.e., if they are peaked near the wall, can generate a new instability which is difficult to stabilize and which leads to diffusion of the impurities into the dust-acoustic plasma
Bibliografija: 12 jed
Sažetak
Keywords: Fizika plazme -- Nestabilnost